Pircēju apmierinātības uzlabošanas iespējas veikalu tīklā ”top!”. - Ilaščuka, Dana (Latvijas Universitāte, 2021)
Bakalaura darba mērķis – pamatojoties uz teorētiskām atziņām un veiktā pētījuma rezultātiem, izpētīt pircēju apmierinātību, par praktisku piemēru izvēloties veikalu tīklu “top!”, atklāt nepilnības pircēju apmierinātībā, sniegt ieteikumus to uzlabošanai. Darbs sastāv no trim nodaļām. Pirmajā autore sniedz pircēju apmierinātības teorētisku skaidrojumu, otrajā tiek raksturots pētāmais uzņēmums “top!”, trešajā nodaļā – apkopoti autores veiktā pētījuma dati. Noslēgumā apkopoti secinājumi un izteikti priekšlikumi.

The aim of the bachelor thesis is to explore buyers’ satisfaction basing on theoretical aspects and survey result, choosing the shop chain “top!” for the case study in order to reveal shortcomings in buyers’ satisfaction and make recommendations for the improvement. The thesis consists of introduction, three chapters, conclusions and proposals. The first chapter analyses the theoretical issues of buyers’ satisfaction and provides the insight in a theoretical explanation of the term. The second chapter describes the research company “top!”. The third chapter sums up the survey results regarding the buyers’ satisfaction. Last, but not least come summarized conclusions and proposals.
Improvement potential for buyers’ satisfaction at shop chain “top!”.
Keywords: Ekonomika un uzņēmējdarbība; buyers; satisfaction; top; shop chain; pircēji